Belgium's historic beer diversity: should we raise a pint to institutions?. Issue 4 (22nd April 2019) - Poelmans, Eline; Taylor, Jason E.
Abstract: Despite its relatively small size, Belgium has historically been considered to have the most diverse array of beer varieties in the world. We explore whether Belgium's institutional history has contributed to its beer diversity. The Belgian area has experienced a heterogeneous and variable array of institutional regimes over the last millennia. In many cases institutional borders crossed through the Belgian area. We trace the historical development of many of Belgium's well-known beer varieties to specific institutional causes. We also show that the geographic production of important varieties, such as Old Brown, Red Brown, Trappist, Lambic, Saison, and Gruitbeer, continues to be influenced by Belgium's institutional past.